Antioxidant and Antimicrobial Properties of the Essential Oil and Extracts of Zanthoxylum alatum Grown in North-Western Himalaya - Sanjay Guleria; A. K. Tiku; Apurva Koul; Sahil Gupta; Gurjinder Singh; V. K. Razdan (The Scientific World Journal)
The essential oil obtained from the fresh leaves of Zanthoxylum alatum was analysed by gas chromatography/mass spectrometry (GC/MS). Fourteen components were identified, and linalool (30.58%), 2-decanone (20.85%), β-fenchol (9.43%), 2-tridecanone (8.86%), β-phellandrene (5.99%), Sabinene (4.82%), and α-pinene (4.11%) were the main components. The EO and methanolic extract of Z. alatum exhibited potent antifungal activity against Alternaria alternata, Alternaria brassicae, and Curvularia lunata. The EO also showed significant antibacterial activity against Bacillus subtilis, Micrococcus luteus, Staphylococcus aureus, and Escherichia coli. Further, antimicrobial constituents of the EO were isolated by bioautography and preparative thin layer chromatography (PTLC) and identified as β-fenchol and linalool using GC/MS analysis. In addition to this, the free radical scavenging activity and antioxidant potential of EO and methanolic extract/fractions of Z. alatum were also investigated using in vitro assays including scavenging ability against DPPH•, reducing power and chelating ability on Fe2+ ions. Our results demonstrate that Z. alatum could be used as a resource of antioxidant and antimicrobial compounds which may find applications in food and pesticide industries.